Perancangan Sistem Informasi Manajemen Modul Front Office Pada Rumah Sakit - Wijaya, Kevin; Oka Sudana, A.A.K.; Dwi Rusjayanthi, Ni Kadek (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.1 April 2015, 2015)
Information systems can be used to provide information quickly. It also can be used by management to make a decisions and to run the hospital’s operations. One of the manual activity that will take a lot of time is for example, searching the data of the patient. It will also waste a lot of space for the file storage. The Design of the Front Office Module of Information System in Hospital was made to support the business processes in the hospital. It also made to replace all the activities that were still done manually in the Front Office Departement. The Method that used to make the system design is TAS (Total Architecture Synthesis) which devided into five steps. The design of the system is integrated with six other modules. The processes in Front Office Module are Data Master Management, Registration, Information, Marketing, Payment, and Reporting. The result of this system design is a design of Modules Relation, Context Diagram, Hierarchy Chart, Overview Diagram, Data Flow Diagram, Database, and Graphical User Interface.
Keywords: Rancangan, Sistem Informasi Rumah Sakit, Modul Front Office, Metode TAS